Pemasangan Sistem Kontrol Otomatis Lampu Penerangan Jalan di Kampung Tani Sengkol Muncul - Erik Agustian Yulanda; Pranoto Budi Laksono; Rini Astuti; Heri Kusnadi; Ojak Abdul Rozak (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Public street lighting (PJU) is an infrastructure that supports community activities at night, as lighting for pedestrians and vehicle users, so as to improve driving safety and comfort, improve environmental security and prevent crime. The existence of PJUs that are not controlled, such as forgetting to turn them off until noon is often the cause of the high consumption of electrical energy. This is often ignored by the public and is considered normal, even though when viewed from the total national energy consumption it has extraordinary consequences. Saving electricity consumption is a solution to the problems faced by the community, with the manufacture and installation of an automatic PJU light control system. The purpose of this PJU lamp automatic control system is to make it easier to operate PJU lamps so as to reduce electrical energy consumption. The stages of implementation in Community Service are a solution to problems by making direct observations to the location to find out the components needed, designing control systems, procuring tools and materials, assembling control panels, installing and testing automatic control systems, providing education to the community. of the importance of controlling the consumption of electrical energy by not neglecting the safety and security of electrical hazards by applying standardization in the use of electrical equipment. The expected results in this Community Service, apart from providing safety and comfort, increasing environmental security and preventing crime as road users, can also provide public understanding and concern for energy saving, safety and security in using electricity.